PENGARUH PERSEPSI ATAS KAMPAYE DIGITAL BOIKOT TERHADAP NIAT BELI ULANG KONSUMEN AQUA YANG DIMEDIASI OLEH CITRA MEREK - Utami Fitri Pangesti; Faizal Fardhani Sigarlaki (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to examine the influence of consumer perceptions of a digital boycott campaign on repurchase intention toward Aqua, with brand image serving as a mediating variable. The boycott campaign, which has circulated on social media since late 2023, has affected public perception of the Aqua brand. This research adopts a quantitative survey approach. The sample consisted of 98 respondents who were aware of the boycott campaign and had previously consumed Aqua products. A purposive sampling technique was employed. Data were collected through questionnaires and analyzed using multiple linear regression. The results indicate that consumer perceptions of the digital boycott campaign have a negative and significant effect on both brand image and repurchase intention. Brand image has a positive effect on repurchase intention and mediates the relationship between boycott perception and repurchase intention. These findings highlight the importance of managing brand image and corporate communication in responding to public opinion in the digital era.